Sixteen common misconceptions about the evolution of cooperation in humans - West, SA; El Mouden, C; Gardner, A (2011)
The occurrence of cooperation poses a problem for the biological and social sciences. However, many aspects of the biological and social science literatures on this subject have developed relatively independently, with a lack of interaction. This has led to a number of misunderstandings with regard to how natural selection operates and the conditions under which cooperation can be favoured. Our aim here is to provide an accessible overview of social evolution theory and the evolutionary work on cooperation, emphasising common misconceptions. © 2011 Elsevier Inc.